System Identification and Seismic Performance Assessment of Representative RC Buildings in Kathmandu Valley - Dhakal, Rajan; Rupakhety, Rajesh; Gautam, Dipendra (Frontiers in Built Environment, 2020)
To identify dynamic characteristics of representative reinforced concrete frame buildings with brick infills, ambient vibration measurements were taken in two four-storied buildings-one situated in soft soil and the another in stiff soil. Non-parametric as well as parametric system identification algorithms were used to estimate vibration frequencies and damping of the two buildings. Numerical models of the buildings were created using the finite element method. Modal frequencies and damping ratios obtained from ambient measurements were used to calibrate and tune the finite element models. The comparison between measured vibration frequencies and those obtained from numerical modelling highlight the need for accuracy in modelling assumptions, in particular, consideration of the stiffness of infill walls and the flexibility of foundation. The finite element models calibrated with system identification results were used estimate response of the two buildings when subjected to strong ground motion recorded at different places in the Valley during the 2015 Gorkha Earthquake. The results show that not considering flexibility of foundation and stiffness of infill walls, as is commonly done in engineering practice, can lead to inaccurate estimates of seismic demand.